Pengaruh Penyuluhan Kesehatan Reproduksi terhadap Pengetahuan dalam Pencegahan Keputihan Patologis di Desa Binor Kecamatan Paiton Kabupaten Probolinggo - Itmam Niamillah; Nova Hikmawati; Homsiatur Rohmatin (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The lack of knowledge about women's problems has made researchers interested in providing solutions and conducting research related to preventing vaginal discharge experienced by adolescents. The purpose of this study was to identify before and after knowledge and to determine the effect of reproductive health education on knowledge in preventing pathological leucorrhoea in Binor Village, Paiton District. This research uses a quantitative approach with the Pre- Test and Post-Test, the sampling used is Cluster random sampling in June 2023 with a total of 40 cases. The results showed that before being given counseling in the good category, there were 16 (40%) respondents. after being given good category counseling as many as 31 (77.5%) respondents. The results of statistical analysis of p-value 0.000 (α> 0.05) show that there is an effect of reproductive health education on knowledge in preventing pathological vaginal discharge in Binor Village, Paiton District. Suggestions to continue to conduct reproductive health counseling in preventing pathological vaginal discharge with appropriate methods.